The rs13064411 polymorphism in the WDR52 gene, associated with PCSK9 levels, modifies statin-induced changes in serum total and LDL cholesterol levels. Issue 3 (March 2015) - de Keyser, Catherine E.; Becker, Matthijs L.; Hofman, Albert; Lous, Jan J.; Uitterlinden, André G.; Visser, Loes E.; Stricker, Bruno H.
Abstract : Objective: Recently, the minor allele of the rs13064411A>G polymorphism in the WD repeat domain 52 ( WDR52 ) gene was associated with increased statin-induced proprotein convertase subtilisin/kexin type 9 (PCSK9) levels and with LDL cholesterol response to statins. PCSK9 promotes LDL receptor degradation, leading to increased serum LDL cholesterol. We investigated whether the polymorphism was associated with cholesterol response to statins. Methods: We identified 1105 current, 322 past, and 4831 never statin users during follow-up in the prospective population-based Rotterdam Study. The mean delta total, LDL, and HDL cholesterol levels between current and no current statin users with the same number of minor alleles were analyzed using random-effect repeated measurements. We adjusted for age, sex, number of cholesterol measurements, and follow-up time. Results: Compared with no users with the same genotype, current statin users carrying a minor allele showed a statistically significantly lower delta total and LDL cholesterol compared with reference homozygous major allele carriers [total: Δ=0.551 mmol/l (AG+GG) vs. Δ=0.732 mmol/l (AA), P interaction : 5.2×10 –7 ; LDL: Δ=0.566 mmol/l (AG+GG) vs. Δ=0.720 mmol/l (AA), P interaction : 1.8×10 –5 ]. The effect was stronger in women ( P interaction : 2.0×10 –5 for LDL cholesterol, 8.0×10 –6 for total cholesterol) and in high-dose users (defined daily doses>1.00) ( P interaction : 7.0×10 –5 for LDL cholesterol, P interaction : 0.081 for total cholesterol). The polymorphism was not associated with HDL cholesterol in current statin users, or with total, LDL and HDL cholesterol in never statin users. Conclusion: The minor G allele of the rs13064411 polymorphism, associated with statin-induced PCSK9-levels, was associated with a decreased LDL-lowering and total cholesterol-lowering response to statins.